Investigation of Large-Diameter Borehole for Enhancing Permeability and Gas Extraction in Soft Coal Seam. (30th December 2020) - Wang, Yongwen; Yan, Wanjun; Ren, Zhongjiu; Yan, Zhiqiang; Liu, Ziwen; Zhang, Heng
Abstract : The efficiency of gas extraction from the soft coal seam with ultralow permeability is low. Gas extraction with large-diameter borehole is proposed to deplete gas content for preventing gas outburst disaster in this study. The fractures around the large borehole will enhance the permeability in the damage area to promote gas extraction. We established a damage-stress-seepage coupling model for large-diameter borehole gas extraction in soft coal seam. This mathematical model contains governing equations of gases sorption and transport, coal deformation, and damage, reflecting the coupling responses between gas and coal seam. The model is solved by the finite element method to simulate the gas drainage large-diameter borehole through roadway. Distributions of elastic modulus, damage area, and maximum principal stress in soft coal seam with different borehole diameters including 94 mm, 133 mm, 200 mm, and 300 mm are analyzed. The gas pressure, gas content, and effective extraction area in soft coal seam are discussed. Results show that the shear failure zone appears around the large-diameter borehole, and its permeability rises sharply. This opens up the gas transport channel and is conducive to the rapid extraction. It is confirmed that gas extraction using large-diameter borehole (300 mm) can greatly improve the efficiency of the gas preextraction in soft coal seam by increasing gas extraction rate. These provide a foundation for guiding the operation of gas extraction with large borehole from the soft coal seam in the field.